Materials processing at casting - Fredriksson, Hasse (Wiley, 2006)
Component casting - Cast house processes - Casting hydrodynamics - Heat transport during component casting - Heat transport in cast house processes - Structure and structure formation in cast materials - Microsegregation in alloys. Peritectic reactions and transformations - Heat treatment and plastic forming - Precipitation of pores and slag inclusions during casting processes - Solidification and cooling shrinkage of metals and alloys - Macrosegregation in alloys.